Efeito da fisioterapia convencional e do feedback eletromiográfico associados ao treino de tarefas específicas na recuperação motora de membro superior após acidente vascular encefálico - Rodrigo Cappato de Araújo; Marcos Pinotti Barbosa (Desafio Singular, 2013)
The purpose of the present study was to evaluate the effects of conventional physical therapy and task specific training associated with electromyographic (EMG) feedback to recover upper limb motor function in patients with hemiparesis caused by stroke. Twelve patients were evaluated and then randomly assigned to either of two groups: Group 1 - Conventional physiotherapy; Group 2 - EMG feedback. Patients attended three weekly 50-min sessions, for eight weeks. The evaluated aspects were motor impairment, motor function, and spasticity, using the Fugl-Meyer Assessment (FMA) test, TEMPA, and the Modified Ashworth Scale (MAS), respectively. Results showed that, in both groups, there were no changes in spasticity in the groups, but there was a significant improvement in FMA values after the rehabilitation programs. Regarding TEMPA scores, only Group 2 presented significant gains. The comparison of the MAS and FMA gains showed no differences between groups. However, group 2 showed greater gains in the two tasks of TEMPA. The results suggest that functional training using EMG feedback can have positive results in improving arm function. However, due to small differences between groups, concluded that EMG/Biofeedback therapy was not superior to other form of treatment.